Fostering Students' Process and Product Creativity Through Chemistry-Based STEM-PjBL in Vocational Context - Fapriyan Mulyopratikno; Antuni Wiyarsi (LUMAT)
This study aims to reveal (1) the level of students' creativity (process and product), (2) description of student’s product in STEM framework. This study applied pre-experimental with one-shot case study design. The samples were 38 male tenth grade students as one group. Teaching intervention was STEM integrated Project Based Learning (STEM-PjBL) model for six meetings. Rubrics of creativity process and product were used to collect the data. The level of students’ creativity was analyzed with categorization descriptively. The results show that students' process creativity is very high, and a few students have a fair process creativity category. Meanwhile, product creativity is fair for students, and a few students have a very low product creativity category. Overall, the automotive vocational students' creativity level is in the Little-Creativity and Mini-Creativity category. All the products produced have integrated STEM, students are more dominant in explaining products using a scientific (chemistry knowledge) dimension, but they are weak in describing the mathematics integrated into the product.